Effect of Carbon Sources and Their Various Concentrations for Optimize in In vitro Micro propagation of Banana Musa (spp.) Basrai - Memon, Amjad Ali; Raza, Ali; Palijo, Shahnawaz; Wenqian, Xiang; Xueyan, Xu (International Journal of Environment, Agriculture and Biotechnology, 2019)
Banana fruit is the second vital food crop. Although the significant business crop value, the major production restrain is the accessibility of reliable and harmless material for planting. For in vitro growth of excited tissues, sources of carbon have been considered as one of the most significant factor. Types of sugars and concentrations are identified to affect the in vitro protocol success. Crop micro propagation is also facing the challenges which require to be addressed in order to improvement in its production. In this study, influence of three carbon sources such as (dextrose, sucrose and sorbitol) used to increase Murashige and Skoog medium at four applications control, 15, 30, 45 and 60g/l respectively. This study is accomplished at the laboratory of tissue culture of Plant Pathology Section, Sindh Agricutlure Research Insitute, Tandojam, Pakistan in 2017. Randomized Block Design (RBD) method with 3 replications was used for each treatment. Results indicated that sucrose give maximum result as compared to dextrose and sorbitol. Though, significant result was found in sucrose 30g/l as compared to dextrose and sorbitol concentrations.